Tricoblastoma Em Cão Jovem (Canis lupus familiaris) - Primeiro Relato De Caso Na República De Moçambique, África - Dos Santos, Ivan Felismino Charas [UNESP]; Cardoso, José Manuel Mota; Soares, Joice Franciele; Assis, Amanda Carla Garcia; Reis, Mariana Gomez; Gomes, Mayara Viana Freire [UNESP]; Tannus, Filipe Carrari Isaac [UNESP] (My University, 2016)
Trichoblastoma is a cutaneous benign neoplasia which is derivate of primitive hair follicles and have epithelial and mesenchymal elements. The study aimed to describe a case of an unusually aggressive trichoblastoma in a male dog, Maltese breed, 7 months old and 7 kg of body weight, with history of increased and rapid growth volume in frontal head region. The neoformation was ulcerated; hard consistency and not adhered; presence of alopecia and pink color; and no pain during palpation. The blood count, serum biochemical tests, urinalysis and imaging exams revealed no changes. On the cytological examination was observed the presence of basal epithelial cells with monomorphic nuclei and basophilic cytoplasm. The treatment was surgery with total excision of the neoformation. Twenty-one months after the surgical procedure was not observed any signs of recurrence and metastasis. Even rare in dogs and with age under 6 years, it was identified a macroscopically aggressive trichoblastoma in young dog with 7 months old, with histopathological features similar to that of adult dogs, and was the first case reported in Mozambique. The total surgical excision of the trichoblastoma was the treatment for this case report.
Trichoblastoma in young dog (Canis lupus familiaris) - First Case Report in Mozambique, Africa
Keywords: Basal cells; Mozambique; Neoplasia; Skin.; Small animals